Spatiotemporal dynamics of HIV-1 CRF63_02A6 sub-epidemic - Sivay, Mariya V.; Maksimenko, Lada V.; Osipova, Irina P.; Nefedova, Anastasiya A.; Gashnikova, Mariya P.; Zyryanova, Dariya P.; Ekushov, Vasiliy E.; Totmenin, Alexei V.; Nalimova, Tatyana M.; Ivlev, Vladimir V.; Kapustin, Dmitriy V.; Pozdnyakova, Larisa L.; et al. (Frontiers in Microbiology, 2022)
1 Abstract HIV-1 epidemic in Russia is one of the fastest growing in the world reaching 1.14 million people living with HIV-1 (PLWH) by in 2021. Since mid-1990s, the HIV-1 epidemic in Russia has started to grow substantially due to the multiple HIV-1 outbreaks among persons who inject drugs (PWID) leading to expansion of the HIV-1 sub-subtype A6 (former Soviet Union (FSU) subtype A). In 2006, a local HIV-1 sub-epidemic caused by the distribution of novel genetic lineage CRF63_02A6 was identified in Siberia. In this study, we used a comprehensive dataset of CRF63_02A6 pol gene sequences to investigate the spatiotemporal dynamic of the HIV-1 CRF63_02A6 sub-epidemic. This study includes all the available CRF63_02A6 HIV-1 pol gene sequences from LANL HIV Sequence Database. The HIV-1 subtypes of those sequences were conferred using phylogenetic analysis, and two automated HIV-1 subtyping tools Stanford HIVdb Program and COMET. Ancestral state reconstruction and origin date were estimated using Nextstrain. Evolutionary rate and phylodynamic analysis were estimated using BEAST v 1.10.4. CRF63_02A6 was assigned for 872 pol gene sequences by using phylogenetic analysis approach. Predominant number (n=832; 95.4%) of those sequences were from Russia; the remaining 40 (4.6%) sequences were from countries of Central Asia. Out of 872 CRF63_02A6 sequences, the corresponding genetic variant was assigned for 75.7% and 79.8% of sequences by Stanford and COMET subtyping tools, respectively. Dated phylogenetic analysis of the CRF63_02A6 sequences showed that the virus most likely originated in Novosibirsk, Russia, in 2005. Over the last two decades CRF63_02A6 has been widely distributed across the Russia and has been sporadically detected in countries of Central Asia. Introduction of new genetic variant into mature sub-subtype A6 and CRF02_AGFSU epidemics could promotes the increase of viral genetic diversity and emergence of new recombinant forms. The fFurther HIV-1 surveillance studies are needed due to a continuing rapid virus distribution. Also, the implementation of HIV-1 prevention programs is required to reduce HIV-1 transmission. This study also highlights the discrepancies in HIV-1 subtyping approaches. The reference lists of HIV-1 sequences implemented in widely-used HIV-1 automated subtyping tools need to be updated to provide reliable results.